Influence of Nitrogen Source Supplementation on Yeast Growth Profile Under Very High Gravity (VHG) Ethanol Fermentation - Fatin Afifah, Adenan (Universiti Malaysia Sarawak (UNIMAS), 2018)
Very high gravity fermentation (VHG) is a technology that use very high concentration of sugar (-270 g/L) to enhance the productivity of ethanol. However, high initial substrate concentration could have adverse effect on the growth of Saccharomyces cerevisiae due to high osmotic pressure. Higher ethanol productivity is expected if higher amount of YE is used as supplement during the VHG fermentation. Instead of using the expensive YE, ammonium sulphate and urea are some cheaper N-sources that could support the growth and viability of yeast under VHG condition. Hence, this research study was conducted to study the influence of nitrogen sources on yeast growth profile, ethanol production and glucose consumption under VHG condition. VHG fermentation was conducted with supplement of different nitrogen sources which is yeast extract (SM + YE), ammonium sulphate (SM + AS), urea (SM + Urea) and without supplement of nitrogen source (standard media, SM) in fermentation media. Yeast growth and its viability were observed through dry cell weight and optical density reading, while ethanol production and glucose consumption were determined through high performance liquid chromatography (HPLC) analysis. Based on the cell concentration obtained from DCW analysis, SM + YE medium gave the highest cell concentration (4.66 g/L), followed by SM + Urea medium (4.56 g/L). However, SM + Urea medium yielded the highest concentration of ethanol (77.77 g/L). Thus, urea have a good potential to replace yeast extract as nitrogen source to aid fermentation process and produce high amount of ethanol.